2010
DOI: 10.4239/wjd.v1.i2.57
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegeneration: An early event of diabetic retinopathy

Abstract: Diabetic retinopathy (DR) has been classically considered to be a microcirculatory disease of the retina caused by the deleterious metabolic effects of hyperglycemia per se and the metabolic pathways triggered by hyperglycemia. However, retinal neurodegeneration is already present before any microcirculatory abn ormalities can be detected in ophthalmoscopic exa mination. In other words, retinal neurodegeneration is an early event in the pathogenesis of DR which predates and participates in the microcirculatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
85
1
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(109 citation statements)
references
References 58 publications
(81 reference statements)
8
85
1
11
Order By: Relevance
“…Usually the first sign of the Müller cell stress is upregulation of glial fibrillary acidic protein (GFAP) content, which may be accompanied by hypertrophy and proliferation under certain damaging conditions. Diabetes itself is able to upregulate GFAP in Müller cells without the presence of other symptoms of DR in humans (Villaroel et al, 2010), and this goes along well with what we see in experimental models where after 2 days of diabetes induction, GFAP upregulation is already apparent (K. Szabadfi, unpublished observation). All the aforementioned observations may lead to the formation of a fourth hypothesis of the initiation of DR, the "glial cells-first" scenario.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Usually the first sign of the Müller cell stress is upregulation of glial fibrillary acidic protein (GFAP) content, which may be accompanied by hypertrophy and proliferation under certain damaging conditions. Diabetes itself is able to upregulate GFAP in Müller cells without the presence of other symptoms of DR in humans (Villaroel et al, 2010), and this goes along well with what we see in experimental models where after 2 days of diabetes induction, GFAP upregulation is already apparent (K. Szabadfi, unpublished observation). All the aforementioned observations may lead to the formation of a fourth hypothesis of the initiation of DR, the "glial cells-first" scenario.…”
supporting
confidence: 63%
“…The deterioration of the intrinsic time and also of oscillatory potentials (OPs) in the electroretinogram (ERG) starts early, in some cases as early as 2 days after induction of diabetes in experimental animals . These observations led to the formulation of the "neurodegeneration-first" hypothesis (Villaroel et al, 2010). Patients suffering from DR experience gradual vision loss; after ERG deterioration, the visually evoked potentials (VEPs) also start to To protect the rights of the author(s) and publisher we inform you that this PDF is an uncorrected proof for internal business use only by the author(s), editor(s), reviewer(s), Elsevier and typesetter SPi.…”
mentioning
confidence: 99%
“…These are suggested by Barber et al, 5 who showed increased apoptosis of retinal neural cells both in experimental diabetic rats and in diabetic patients. Increased apoptosis is probably due to the following: (i) neurofilament accumulation in RGC axons, related to changes in retrograde axonal transport; 26 (ii) elevated levels of glutamate; (iii) increasing neurotoxic factors, 27 and (iv) reactive changes in microglia. 28 Moreover, comparing patients without abnormalities on the RNFL and GC-IPL analysis with healthy controls, we found a significant GC-IPL and RNFL thickness reduction.…”
Section: P-valuementioning
confidence: 99%
“…Neuronal degeneration patterns have been observed in various animal models of diabetes, and early retinal dysfunction has been demonstrated (3,4). Postmortem studies in humans have revealed neuronal degeneration and apoptosis in retinas, mainly in the ganglion cell layer (5,6).…”
mentioning
confidence: 99%